Analisis Penyusunan Laporan Keuangan Pada Usaha Mikro Kecil dan Menengah Berdasarkan SAK EMKM Pada Usaha Aisyah Loundry - Amalia Susanti, Sheka; Hariany Idris; Mukhammad Idrus (STIEM BONGAYA, 2025)
This study aims to assist in the preparation of financial reports for the Aisyah laundry micro business based on SAK EMKM. The focus of this study is to find out how the preparation of financial reports is carried out by the Aisyah laundry micro business based on SAK EMKM. This research method is descriptive qualitative. Data obtained by conducting interviews, and documentation related to the problems studied. The results of the study concluded that: the preparation of financial reports carried out by the Aisyah Laundry Micro Business is still very inconsistent with the EMKM SAK because the recording of financial reports carried out is not in accordance with the accounting cycle and does not have a single type of financial report that is in accordance with accounting standards. This shows that the Aisyah Laundry Micro Business has not been able to measure the level of financial performance of its business